Excitation of long-wavelength surface optical vibrational modes in films, cubes and film/cube composite system using an atom-sized electron beam. (23rd January 2018) - Lagos, Maureen J; Trügler, Andreas; Amarasinghe, Voshadhi; Feldman, Leonard C; Hohenester, Ulrich; Batson, Philip E
Abstract : We investigate the excitation of surface optical vibrational modes in amorphous silicon dioxide films and magnesium oxide nanocubes in the long-wavelength regime with keV electrons. We show that the response of these nanosystems is strongly constrained by their size and shape and can be explained by the dielectric characteristics of the involved materials. Abstract: Using spatially resolved Electron Energy-Loss Spectroscopy, we investigate the excitation of long-wavelength surface optical vibrational modes in elementary types of nanostructures: an amorphous SiO2 slab, an MgO cube, and in the composite cube/slab system. We find rich sets of optical vibrational modes strongly constrained by the nanoscale size and geometry. For slabs, we find two surface resonances resulting from the excitation of surface phonon polariton modes. For cubes, we obtain three main highly localized corner, edge, and face resonances. The response of those surface phonon resonances can be described in terms of eigenmodes of the cube and we show that the corresponding mode pattern is recovered in the spatially resolved EELS maps. For the composite cube/substrate system we find that interactions between the two basic structures are weak, producing minor spectral shifts and intensity variations (transparency behaviour), particularly for the MgO-derived modes.